ICT IN IMPROVING READING COMPREHENSION IN UNIVERSITY STUDENTS AT FEDERICO VILLARREAL NATIONAL UNIVERSITY, LIMA, PERU - Campos-Pérez, Rosalvina (2021)
The objective of this work was to analyze how the use of Information and Communication Technology (ICT) improves and increases the development of reading comprehension at the inferential and critical levels in students of the 3rd semester of 2020 of the Faculties of Social Sciences and Humanities of the National University Federico Villarreal. The research was of an explanatory level and the design used was quasi-experimental. The simple consisted of 74 students from the two faculties who were selected for convenience, with whom the control group (30) and the experimental group (44) were formed. Pretest and posttest tests were applied to both groups with the difference that the control group was not trained. Regarding the variable use of ICT, these contribute to the improvement of learning and increase and improve the development of reading comprehension at the inferential level but not the critical level in students. Keywords: reading comprehension – ICT – inferential level – critical level